2020
DOI: 10.1007/978-3-030-62807-9_14
|View full text |Cite
|
Sign up to set email alerts
|

Smart Dust in the Industrial Economic Sector – On Application Cases in Product Lifecycle Management

Abstract: Smart dust is an autonomous sensing, computing, and communication system that can be packed into a cubic-millimeter mote to form the basis of integrated, massively distributed sensor networks. The purpose of this manuscript is to identify potential applications of smart dust in product lifecycle management with a focus on the industrial economic sector. Resting upon empirical data from the European DACH region, we describe six applications: (1) Advancement of requirements engineering, (2) Improvement of manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For the iterative conceptualization, we continuously referred to established concepts (e.g., product-service-continuum (Baines et al, 2007), product/service development (Ansoff, 1957)). In sum, we chose dimension 1 as "Product" and dimension 2 as "Service" because both empirical evidence and knowledge base showed that smart dust affords product and service innovation alike (Holler et al, 2020a(Holler et al, , 2020bIlyas & Mahgoub, 2018). Furthermore, these dimensions were differentiated into the states "No product/service", "Existing product/service" and "Smart dust-enhanced product/service" as industrial enterprises typically start with an existing offering striving to complement and improve it (Lerch & Gotsch, 2015).…”
Section: Three Strategies and Their Applicationmentioning
confidence: 99%
See 3 more Smart Citations
“…For the iterative conceptualization, we continuously referred to established concepts (e.g., product-service-continuum (Baines et al, 2007), product/service development (Ansoff, 1957)). In sum, we chose dimension 1 as "Product" and dimension 2 as "Service" because both empirical evidence and knowledge base showed that smart dust affords product and service innovation alike (Holler et al, 2020a(Holler et al, , 2020bIlyas & Mahgoub, 2018). Furthermore, these dimensions were differentiated into the states "No product/service", "Existing product/service" and "Smart dust-enhanced product/service" as industrial enterprises typically start with an existing offering striving to complement and improve it (Lerch & Gotsch, 2015).…”
Section: Three Strategies and Their Applicationmentioning
confidence: 99%
“…Comprising the whole IoT technology stack from sensor to service, these motes can be installed in the application range of industrial assets to expedite sensing to the next level (Ilyas & Mahgoub, 2018). Reverting to related literature, recent empirical works (Holler et al, 2020a(Holler et al, , 2020b explored the economic potentials of smart dust in industrial settings. More precisely, Holler et al (2020aHoller et al ( , 2020b showed opportunities across the whole lifecycle, from beginning-of-life (e.g., advancement of requirements engineering) over middle-of-life (e.g., enhancement of logistics monitoring) to end-oflife (e.g., augmented retirement planning).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, it has received a considerable amount of attention from the research community because many remote sensing applications can benefit from this technology for monitoring rough terrains such as forests, frozen lands, mountains, sea, space, planets, etc. [22][23][24][25]. For example, environmental researchers can use this technology for monitoring air quality, pollution, carbon, or any chemical substances in the air.…”
Section: Introductionmentioning
confidence: 99%